2015
DOI: 10.1890/14-1261.1
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and biogeographic null hypotheses for comparing rarefaction curves

Abstract: The statistical framework of rarefaction curves and asymptotic estimators allows for an effective standardization of biodiversity measures. However, most statistical analyses still consist of point comparisons of diversity estimators for a particular sampling level. We introduce new randomization methods that incorporate sampling variability encompassing the entire length of the rarefaction curve and allow for statistical comparison of i !2 individual-based, sample-based, or coverage-based rarefaction curves. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 70 publications
(87 reference statements)
0
71
1
Order By: Relevance
“…Rarefaction curves were used to confirm that sufficient sequencing coverage had been achieved, and to identify differences of species diversity between groups. Significant differences between rarefaction curves of different groups were calculated as described by Cayuela et al 33 using the function EcoTest.sample from R package rareNMtests v1.1. Alpha diversity is a measure of microbiota abundance and how evenly these are distributed (evenness), and was estimated through Shannon's diversity index.…”
Section: Bioinformatic Microbiota Analysesmentioning
confidence: 99%
“…Rarefaction curves were used to confirm that sufficient sequencing coverage had been achieved, and to identify differences of species diversity between groups. Significant differences between rarefaction curves of different groups were calculated as described by Cayuela et al 33 using the function EcoTest.sample from R package rareNMtests v1.1. Alpha diversity is a measure of microbiota abundance and how evenly these are distributed (evenness), and was estimated through Shannon's diversity index.…”
Section: Bioinformatic Microbiota Analysesmentioning
confidence: 99%
“…This suggested that space‐for‐time substitutions can be invalid for assessing ecological responses to urbanization and supports the value of historical land‐use data for assessing patterns in biodiversity change (Harding, Benfield, Bolstad, Helfman, & Jones, ). Implementing multiple scales of resolution into assemblage change with multiple Hill numbers is an effective method for measuring spatial and temporal changes in assemblage structure (Cayuela et al, ), and can be combined with functional trait data to assess potential mechanisms that might be contributing to observed assemblage change (Crumby, Webb, Bulow, & Cathey, ; Hoeinghaus, Winemiller, & Birnbaum, ). Our approach here suggests that combining a riverscape perspective with new rarefaction‐based analyses is a promising avenue for identifying the spatiotemporal extents of change in stream fish assemblages.…”
Section: Discussionmentioning
confidence: 99%
“…While there are standard methods to extrapolate the number of species (Colwell and Coddington , Chao et al ) and compare the overall shape of rarefaction curves (Cayuela et al ), we were interested in the statistical differences between our rarefaction curves across the range of resampled levels. To assess differences between the control and migration treatments, we conducted a bootstrapping procedure to compare the difference in the mean number of species at every resampling level, x i , along the rarefaction curves.…”
Section: Methodsmentioning
confidence: 99%